Human Papillomavirus Status of Head and Neck Squamous Cell Carcinoma Patients and its Association with Expression of PIK3CA and CRNDE - Laleh Karimi Sani (Shiraz University of Medical Sciences, 2021)
Background: Human papillomavirus (HPV) positive head and neck squamous cell carcinoma (HNSCC) have distinctive molecular features. We conducted the present work to evaluate the HPV status of HNSCC patients and its association with expression of PIK3CA and CRNDE genes. Method: In the present case-control study, 50 fresh frozen tissue samples of HNSCC patients were collected from the patients referred to hospital for tumor removal. HPV typing was performed on DNA samples using a one-step polymerase chain reaction (PCR) followed by Reverse Line Blot method. Relative expression of PIK3CA and CRNDE genes was evaluated utilizing a real-time PCR method. Results: Out of 50 patients, 14 (28%) were HPV positive and the most prevalent type was HPV 16. Both PIK3CA and CRNDE genes were upregulated in tumoral tissues compared with adjacent non-cancerous tissues (ANCTs) (P=0.0322 and 0.0005, respectively). Based on the area under curve (AUC) values, the diagnostic power of CRNDE (AUC= 0.676) was higher than that of PIK3CA (AUC= 0.604). Finally, the expression level of PIK3CA was significantly associated with HPV+ HNSCC (P=0.01). Conclusion: We showed that the prevalence of HPV in HNSCC was within our local prevalence range. Moreover, the association of PIK3CA overexpression with HPV status implied distinctive molecular characteristics of HPV(+) HNSCC.